Small cell neuroendocrine carcinoma and poorly differentiated rhabdomyosarcomas of the urinary bladder in adults—A comparative analysis in favor of a common histogenesis - Bahlinger, Veronika; Stöhr, Robert; Hartmann, Arndt; Hes, Ondřej; Agaimy, Abbas (Virchows Archiv, 2024)
Rhabdomyosarcoma (RMS) of the urinary bladder in adults and elderly is an exceptionally rare neoplasm that displays poorly differentiated solid (alveolar-like) small cell pattern, frequently indistinguishable from small cell neuroendocrine carcinoma (SCNEC). However, the histogenesis of RMS and SCNEC and their inter-relationship have not been well studied and remained controversial. We herein analyzed 23 SCNEC and 3 small round cell RMS of the bladder for neuroendocrine (synaptophysin + chromogranin A) and myogenic (desmin + myogenin) marker expression and for TERT promoter mutations. In addition, the RMS cohort and one SCNEC that was revised to RMS were tested for gene fusions using targeted RNA sequencing (TruSight Illumina Panel which includes FOXO1 and most of RMS-related other genes). Overall, significant expression of myogenin and desmin was observed in one of 23 original SCNEC justifying a revised diagnosis to RMS. On the other hand, diffuse expression of synaptophysin was noted in 2 of the 4 RMS, but chromogranin A was not expressed in 3 RMS tested. TERT promoter mutations were detected in 15 of 22 (68%) SCNEC and in two of three (67%) assessable RMS cases, respectively. None of the four RMS cases had gene fusions. Our data highlights phenotypic and genetic overlap between SCNEC and RMS of the urinary bladder. High frequency of TERT promoter mutations in SCNEC is in line with their presumable urothelial origin. In addition, the presence of TERT promoter mutation in 2 of 3 RMS and lack of FOXO1 and other gene fusions in all 4 RMSs suggest a mucosal (urothelial) origin, probably representing extensive monomorphic rhabdomyoblastic transdifferentiation in SCNEC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: FOXO1 gene fusions; Rhabdomyosarcoma; Small cell neuroendocrine carcinoma; TERT promoter mutations; Urinary bladder